2018
DOI: 10.1007/s10787-017-0438-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of nanoemulsions of essential oil from Rosmarinus officinalis L.: in vitro and in zebrafish studies

Abstract: The essential oil from Rosmarinus officinalis L. (OERO) has bioactive compounds with anti-inflammatory activity. The objective of this study was to evaluate the anti-inflammatory potency of nanoemulsions containing essential oil of Rosmarinus officinalis L. (NOERO, NECHA, NECULT, and NECOM) in vitro and in vivo. This study was accomplished in a quantitative format through tests with diphenyl picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS), cellular antioxidant activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(113 citation statements)
references
References 55 publications
6
107
0
Order By: Relevance
“…REO-NLCs and REO similarly showed maximum efficiency against Gram-positive bacteria. Borges et al [21] showed that Gram-positive bacteria were more susceptible to nanoemulsions of essential oil than Gram-negatives. This could be attributed to the fact that the lipophilic ends of lipoteichoic acids in the cell wall of Gram-positives facilitate the penetration of hydrophobic compounds [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…REO-NLCs and REO similarly showed maximum efficiency against Gram-positive bacteria. Borges et al [21] showed that Gram-positive bacteria were more susceptible to nanoemulsions of essential oil than Gram-negatives. This could be attributed to the fact that the lipophilic ends of lipoteichoic acids in the cell wall of Gram-positives facilitate the penetration of hydrophobic compounds [21].…”
Section: Discussionmentioning
confidence: 99%
“…Borges et al [21] showed that Gram-positive bacteria were more susceptible to nanoemulsions of essential oil than Gram-negatives. This could be attributed to the fact that the lipophilic ends of lipoteichoic acids in the cell wall of Gram-positives facilitate the penetration of hydrophobic compounds [21]. Nanoparticle properties may enhance the passive cellular absorption mechanisms and also decrease mass transfer resistances [22].…”
Section: Discussionmentioning
confidence: 99%
“…Electrospray ionization‐mass spectrometry (ESI‐MS), UV–Vis spectrophotometer, high‐performance liquid chromatography (HPLC), Fourier‐transform infrared (FTIR), and comparative spectroscopic literature analysis were all used to authenticate the purity of TPAR. The concentration of TPAR was estimated using dual‐wavelength spectrophotometry (UV 2600 Shimadzu, Kyoto, Japan) as reported with slight modifications (Borges et al, ; Gupta, Ghosh, Maiti, & Mahua, ; Marwada et al, ). Two wavelengths were selected based on the principle that the difference in absorbance of two points on the overlain spectra is directly proportional to the concentration of the component of interest.…”
Section: Methodsmentioning
confidence: 99%
“…The chemical shifts of TPAR were assigned with reference to the internal standard, CDCl 3 , (Cao et al, 2007;Sassano et al, 2009;Siano, Addeo, et al, 2016), which was assumed to resonate at δH 7.26 (CHCl 3 impurity) and δC 77.00 ppm, respectively. The thin-layer chromatography (TLC) was also used to evaluate the separation efficiency via pre-coated silica gel plates using (Borges et al, 2018;Gupta, Ghosh, Maiti, & Mahua, 2011;Marwada et al, 2014).…”
Section: Analysis Of Tparmentioning
confidence: 99%
See 1 more Smart Citation